2006
DOI: 10.2320/matertrans.47.2918
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of High Strength Al-Mg-Si Alloy during Solidification

Abstract: Mechanical properties of high strength Al-Mg-Si alloy during solidification have been investigated. Tensile strength and ductility have been measured by using an electromagnetic induction heating tensile machine. The relation between solid fraction and temperature was calculated by the Gulliver-Scheil model applied with the thermodynamic data-base Thermo-Calc for multi-component system, and its validity was confirmed, comparing with the experiment. Zero Strength Temperature (ZST) and Zero Ductility Temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Chemical compositions of cast billet are given in Table 1. In comparison with previously reported alloy (HS60), 11,16) Magnesium, silicon and copper contents in this alloy were decreased from 1.12 to 0.83 mass%, from 1.23 to 1.0 mass% and from 0.79 to 0.40 mass%, respectively, to reduce the hot tearing. The samples for microstructure observation were taken from the billet after casting and the crystallized phases were investigated by X-ray diffraction method (XRD) and electron probe micro analysis (EPMA).…”
Section: Casting Experimentscontrasting
confidence: 47%
See 1 more Smart Citation
“…Chemical compositions of cast billet are given in Table 1. In comparison with previously reported alloy (HS60), 11,16) Magnesium, silicon and copper contents in this alloy were decreased from 1.12 to 0.83 mass%, from 1.23 to 1.0 mass% and from 0.79 to 0.40 mass%, respectively, to reduce the hot tearing. The samples for microstructure observation were taken from the billet after casting and the crystallized phases were investigated by X-ray diffraction method (XRD) and electron probe micro analysis (EPMA).…”
Section: Casting Experimentscontrasting
confidence: 47%
“…5, the phase formation sequence during solidification comparing the solidification sequence between HS65 (present study) and HS60 (previous study), a small reduction of the content of magnesium, silicon and copper, resulted in the crystallization of (AlFeSi) prior to Mg 2 Si. 16) In order to confirm the calculated results, several temperatures were selected for the quenching test (quenched temperatures as indicated in Fig. 6) and the quenched samples were analyzed by XRD and EPMA.…”
Section: Resultsmentioning
confidence: 89%
“…According to the previous reports, 4,5) the wider solidification temperature range causes higher crack sensitivity of the alloys. However, we found that the solidification temperature range was not sufficient to estimate the crack sensitivity, at least for A3000 and A5000 series aluminum alloys.…”
Section: Introductionmentioning
confidence: 73%
“…It is advisable to alloy aluminum-magnesium alloys with silicon, which is included in a number of branded alloys (for example, 512) with a content of 1.5-2% [1,[5][6][7]. Silicon (Si) maintains a low density (it forms, with magnesium (Mg), the Mg 2 Si phase, the density of which is only 1.88 g/cm 3 [2]) and high corrosion resistance, while also increasing the hardness and casting properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%